Maintenance engineering and management - appendix 12.A1: indicative economic life expectancy. CIBSE Guide M supplement: January 2020. (Guide M Supplement, 2020)
A supplement to CIBSE Guide M, this is an updated version of appendix 12.A1 which includes more recent life expectancy data.